A Genome-Wide Association Study of Novel Genetic Variants Associated With Anthropometric Traits in Koreans - Cho, Hye-Won; Jin, Hyun-Seok; Eom, Yong-Bin (Frontiers in Genetics, 2021)
Most previous genome-wide association studies (GWAS) have identified genetic variants associated with anthropometric traits. However, most of the evidence was reported in European populations. Anthropometric traits such as height and body fat distribution are significantly affected by gender and genetic factors. Here, we performed GWAS involving 64,193 Koreans to identify the genetic factors associated with anthropometric phenotypes including height, weight, body mass index (BMI), waist circumference, hip circumference, and waist-to-hip ratio (WHR). We found nine novel single nucleotide polymorphisms (SNPs) and 59 independent genetic signals in genomic regions that were reported previously. Of the 19 SNPs reported previously, eight genetic variants at RP11-513I15.6 and one genetic variant at the RP11-977G19.10 region, and six Asian-specific genetic variants were newly found. We compared our findings with those of previous studies in other populations. Five overlapping genetic regions (PAN2, ANKRD52, RNF41, HGMA1, and C6orf106) had been reported previously but none of the SNPs independently identified in the current study. Seven of the nine newly found novel loci associated with height in women revealed statistically significant skeletal expression of quantitative trait loci (eQTL). Our study provides additional insight into the genetic effects of anthropometric phenotypes in East Asians.